Correction: Increasing incidence of mucormycosis in a large Spanish hospital from 2007 to 2015: Epidemiology and microbiological characterization of the isolates. - Jesús Guinea; Pilar Escribano; Antonio Vena; Patricia Muñoz; María Del Carmen Martínez-Jiménez; Belén Padilla; Emilio Bouza (PLoS ONE, 2020)
[This corrects the article DOI: 10.1371/journal.pone.0179136.].